Quantifying and modelling the ENSO phenomenon and extreme discharge events relation in the La Plata Basin. Issue 1 (2nd January 2021) - Meis, Melanie; Llano, María Paula; Rodriguez, Daniela
ABSTRACT: Understanding and monitoring extreme events is essential, particularly in river discharges from the La Plata Basin, where a large percentage of the economic resources and population of the region are concentrated. In this article, we seek to quantify the relationship between extreme events in discharge and the seasonal climatic index NIÑO 3.4. We start by estimating the phase shift between the index and mean seasonal (trimester) discharge values. Based on this result, we align the series and use the copula method to fit a joint distribution. We end up with a model that is particularly useful for quantifying the probability of occurrence of extreme events and monitoring their return periods. As a final step, we generate predictions and validate the model by splitting the series into training and test datasets. We develop a simple effective model for monitoring discharges using the El Niño Southern Oscillation (ENSO) index.